The Role Of The Altman Z-Score Method To Predicate The Bankruptcy Of KUD Sumber Wangi Pamekasan - Maulana, Wahyu; Purwanto, Purwanto; Surya, Citra Larashati (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2023)
To meet the needs of life, the community relies on the KUD whose aim is to ensure the needs and welfare of the community with a people's economic movement based on people's and kinship. In its development, KUD also experienced difficulties in developing its business caused by: 1. Lack of understanding of cooperatives, resulting in misunderstandings; 2. Macro and political approach in cooperative development. The purpose of this study is to analyze the KUD whose condition is not good as an evaluation material and take the right strategy to improve future conditions. The research method is descriptive quantitative. The analysis tool uses the altman z-score method. The results showed that the KUD condition was in a safe position in 2017 to 2021 even though in 2019 it was in a gray area due to the covid period in that year which resulted in KUD having to work hard to improve its performance at that time